Aeolian transport and deposition of carbonaceous aerosols over the Northwest Pacific Ocean in spring. (15th February 2020) - Wu, Zilan; Hu, Limin; Guo, Tianfeng; Lin, Tian; Guo, Zhigang
Abstract: The present study provides insight into the long-range transport of carbonaceous aerosols over the Northwest Pacific Ocean (NWP) based on marine aerosol samples collected onboard a research vessel in the spring of 2015. Organic carbon (OC) and elemental carbon (EC) concentrations showed maxima in proximity to land, with high levels also observed in advective air masses. The decoupled spatial variations in OC and EC levels in relatively pristine air masses from the Pacific, in which aerosol n -alkanes of marine origin were relatively high in abundance, revealed the influence of heterogeneity in air masses and suggested the release of n -alkanes from local marine environments. This was confirmed by the enhanced particle-bound fraction of marine organic matter-sourced n -alkanes, resulting in non-significant relationships between the gas–particle partition coefficient of n -alkanes and the corresponding sub-cooled liquid vapor pressure in some marine air masses. High OC/EC ratios over the NWP indicated secondary organic aerosol formation, possibly as a result of marine emissions followed by gas-to-particle conversion and/or aerosol aging during long-range transport from East Asia. Similar molecular profiles of n -alkanes were found in air and seawater particles in regions dominated by either marine or continental influence, reflecting the strengths of continental and/or marine input and more importantly, suggesting the occurrence of air–sea exchange through wind-induced marine emissions or atmospheric deposition. Relative to the East China Sea, dry particle deposition after long-range transport acted as a more important source for terrestrial lipids in the open NWP. Graphical abstract: Image 1 Highlights: Long-range transported carbonaceous aerosols from East Asia deeply perturb the atmospheric conditions over the NWP in spring. Episodic exchange of n -alkanes at the air–sea interface occurs through wind-induced marine emission or dry particle deposition. Air-to-sea deposition of organic aerosols from East Asia acts as an important source of terrestrial lipids in the open NWP.